2021
DOI: 10.34172/jlms.2021.57
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Between the efficacy of Long-Pulsed Neodymium- YAG Laser and Fractional Co2 Laser in the Treatment of Striae Distensae

Abstract: Introduction: Stretch marks, or striae distensae (SD), are the lesions of the dermis caused by its linear atrophy at the sites of stretching. They occur in more than 70% of pregnant women and adolescents as a result of cutaneous stretching. This study aimed at evaluating and comparing the clinical and histological efficacy of the fractional CO2 laser versus the long pulsed (LP) Nd: YAG laser in the treatment of striae alba. Methods: Thirty female subjects having bilateral symmetrical stretch marks were managed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…3 Fractional treatments, such as fractional radiofrequency (FRF) and ablative fractional laser (AFL), performed better in remodeling the dermis. 4,5 Recently, nonablative fractional laser (NAFL) and AFL (2940-nm Er:YAG laser, ablative 10 600 nm carbon dioxide fractional laser) have been shown to be effective in improving SD. 5,6 In 2018, our research team found a significant clinical benefit in utilizing a combination of 2940-nm Er:YAG AFL with LED-RL and rb-bFGF for treating SA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Fractional treatments, such as fractional radiofrequency (FRF) and ablative fractional laser (AFL), performed better in remodeling the dermis. 4,5 Recently, nonablative fractional laser (NAFL) and AFL (2940-nm Er:YAG laser, ablative 10 600 nm carbon dioxide fractional laser) have been shown to be effective in improving SD. 5,6 In 2018, our research team found a significant clinical benefit in utilizing a combination of 2940-nm Er:YAG AFL with LED-RL and rb-bFGF for treating SA.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the success of photoelectric treatments for scarring and rhytides, photoelectric treatments have been applied to SD to achieve a similar level of effectiveness 3 . Fractional treatments, such as fractional radiofrequency (FRF) and ablative fractional laser (AFL), performed better in remodeling the dermis 4,5 . Recently, non‐ablative fractional laser (NAFL) and AFL (2940‐nm Er:YAG laser, ablative 10 600 nm carbon dioxide fractional laser) have been shown to be effective in improving SD 5,6 .…”
Section: Introductionmentioning
confidence: 99%